2022
DOI: 10.13189/saj.2022.100609
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perspectives on Promoting Physical Activity in Early Childhood Education: A Pilot Study in Indonesia

Abstract: Teachers have a vital role in children's development. This study aims to collect the perspectives of early childhood education teachers on 1) the importance of their roles and responsibilities in promoting physical activity; 2) their understanding of various physical activities; and 3) their interest in physical activity training. An online survey was employed to obtain a quantitative description of the data and open-ended questions to obtain feedback in the form of early childhood education teacher comments t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Then, it was also related to the difficulty in implementing the learning model as a whole because of the characteristics of elementary school students who want to play directly and the difficulty in implementing ICT media in Physical Education learning which is dominated by games/movements. In line with this, previous research in Preschools regarding teacher perspectives on existing facilities and infrastructure revealed that they needed adequate spaces, both indoors and outdoors, to support learning and facilities in the form of educational teaching aids to support physical motor activities (Nur et al, 2022). The results of other studies added that the preparation of adequate facilities and infrastructure that could be used mobile could make it easier for teachers to facilitate physical activity activities in schools apart from teacher behaviors and increasing training/education about physical activity activities for teachers would be beneficial (Hesketh et al 2017;Martyniuk & Tucker, 2014).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Then, it was also related to the difficulty in implementing the learning model as a whole because of the characteristics of elementary school students who want to play directly and the difficulty in implementing ICT media in Physical Education learning which is dominated by games/movements. In line with this, previous research in Preschools regarding teacher perspectives on existing facilities and infrastructure revealed that they needed adequate spaces, both indoors and outdoors, to support learning and facilities in the form of educational teaching aids to support physical motor activities (Nur et al, 2022). The results of other studies added that the preparation of adequate facilities and infrastructure that could be used mobile could make it easier for teachers to facilitate physical activity activities in schools apart from teacher behaviors and increasing training/education about physical activity activities for teachers would be beneficial (Hesketh et al 2017;Martyniuk & Tucker, 2014).…”
Section: Discussionmentioning
confidence: 56%
“…The questionnaire instrument was adapted from previous research (Burgueño et al, 2022;Nur et al, 2022;Wallhead et al, 2021) and had been validated and analyzed using the item fit order procedure through Rasch modeling as shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…For this, it is necessary to develop such means and methods of physical education that would correspond to their individual psychophysiological characteristics [5]. The types of physical activity that are suitable for the student in terms of the characteristics of his nervous system will more quickly cause positive emotions when they are performed compared to those exercises that do not correspond to the individual characteristics of higher nervous activity [6][7][8][9]. And, if the type of physical activity suits a person, he will do it on his own.…”
Section: Introductionmentioning
confidence: 99%
“…Each pedagogical specialty has its own characteristics [5]. Thus, a primary school teacher, just like teachers of preschool education, is a special category of teachers [6,7]. Their profession is distinguished by the need to possess a wide arsenal of knowledge from various fields.…”
Section: Introductionmentioning
confidence: 99%